Combined effects of external mass transfer and biodegradation rates on removal of phenol by immobilized Ralstonia eutropha in a packed bed reactor - Tepe, Ozlem; Dursun, Arzu Y. (Elsevier Science Bv, 2008)
Biodegradation of phenol by calcium-alginate immobilized Ralstonia eutropha was carried out in a batch stirred and a packed bed reactor. In the batch system studies, the effect of initial phenol concentration on biodegradation was investigated at 30 degrees C and pH 7 while in the continuous system studies, the effects of flow rate and inlet phenol concentration on biodegradation were tested at the same temperature and pH. The observed biodegradation rate constant was calculated at different flow rates with the assumption of first-order biodegradation kinetics. Various external mass transfer correlations were evaluated and a new correlation of the type J(D) = K(N-Re)(-(n-1)) was developed with the values of K = 1.34 and n = 0.65. The intrinsic first-order biodegradation rate constants and the external mass transfer coefficients were calculated then the combined effects of these rates on the observed first-order biodegradation rate constants were also investigated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: phenol; Ca-alginate gel-immobilized Ralstonia eutropha; biodegradation; packed bed reactor; external mass transfer coefficient